Effects of milk thistle and flaxseed oils obtained by the methods of cold and hot pressings on the state of colon under acute colitis in rats - Kuznіetsova, H.M.; Denis, E.O.; Moskalets, T.Z.; Rybalchenko, V.K. (Reports of the National Academy of Sciences of Ukraine, 2017)
The effects of consumption of cold-pressed (43—45 ºC) and hot-pressed (95 ºC) flaxseed and milk thistle oils on the development of acute colitis in rats are investigated. It is shown that cold- and hot-pressed flaxseed and hotpressed milk thistle oils significantly prevent the development of inflammatory, destructive, and degenerative changes in colon mucosa. These oil properties could be realized partially by unsaturated fatty acids, in particular ω3, including minor ones.